Socio-Cultural Dynamics of Resilience Building: Lesson Learned from Sleman, Indonesia - Agusma Putri Wardani; Bevaola Kusumasari (Magister Ilmu Administrasi Publik, 2019)
The eruption of Mount Merapi in 2010 was one of the largest volcanic eruptions in Indonesian history. The catastrophic event resulted in fatalities, loss of homes and livelihoods, infrastructure damage, and trauma for residents. There also a shift in community dynamics. The purpose of this study is to analyse and understand the formation of resilient communities by examining the shift in the society dynamics, specifically socio-cultural changes in community-based interventions. The study is a case study of Pangukrejo Hamlet in Sleman, Indonesia. Study results showed that in the aftermath of the eruption, the community experienced changes in degree of harmony and mutual respect among members. The study identified community economy dynamics, which are attributable to three interventions. Study results formed the basis for drawing policy implications for public awareness of disaster risk and post-disaster recovery in general.